Pengaruh Penerapan Metode The Power Of Two Pada Pembelajaran Menulis Teks Biografi Siswa Kelas X SMAN 19 Gowa - Heri Sutrismin; Rosmini Madeamin; Muhammad Nurahmad (LPPM Politeknik Pratama, 2023)
The main problem in this study is whether The Power Of Two Method affects the ability to write biographical texts for Class X students of SMAN 19 Gowa. This study aims to determine the effect of The Power Of Two method on the Ability to Write Biographical Texts of Class X Students of SMAN 19 Gowa. This type of research is experimental research with the pre-experimental method, the research design is the one group pretest posttest, which is a type of research that only involves 1 class as an experimental class which is carried out without a comparison group. The sample in this study was class X students totaling 36 students. Based on the results of research and data analysis regarding this statistical comparison, comparisons with categories of learning outcomes and comparisons of completeness levels prove an increase in student learning outcomes in class X SMAN 19 Gowa can be seen from student learning outcomes through descriptive statistical analysis before using the The Power Of Two learning model. the average student score is still below the KKM, which is 63.2 and after using the learning model The Power of Two, the average student score increases above the KKM 84.5. It is known that the Posttest value is 84.5 more than the Prest value which is 63.2. Furthermore, based on the results of inferential statistical analysis using the t-test formula, it is known that the tcount obtained is 3.367 with a frequency of df = 28-1 = 27, at a significant level of 0.05 or 5%, the ttable is 1.701. So tcount> ttable or HO has been tested and H1 is accepted. Based on these results it can be concluded that there is a significant increase in student learning outcomes. This means that the use of The Power Of Two learning method has an effect on the ability to write biographical texts in class X students of SMAN 19 Gowa. Keywords: influences, The Power Of Two, Biographical Texts